1996
DOI: 10.1524/ract.1996.75.3.149
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Specific Sorption of Neptunium(V) on Smectite in Low pH Solution

Abstract: The "specific sorption" of neptunium(V) on smectite, in other words, a strong sorption undesorbable by 1 M KCl, is studied with a combination of batch type sorption and desorption experiments over a pH range of 2 to 5. Six types of homoionic smectite (Li-, Na-, Κ-, Cs-, Mg-, and Ca-smectite) are used in this study. Distribution coefficients (K d ) of neptunium for smectite vary over a wide pH range; the maximum K d value of ~300 cm 3 · g _1 at around pH 2 for Li-and Na-smectite and the minimum value of ~2cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…The preparation of homoionic Na + -montmorillonite (Na-montmorillonite) and Ca 2+ -montmorillonite (Ca-montmorillonite) is described elsewhere. 4) For comparison, synthetic α-FeOOH (Junsei Chemical Co. Ltd.) was also used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of homoionic Na + -montmorillonite (Na-montmorillonite) and Ca 2+ -montmorillonite (Ca-montmorillonite) is described elsewhere. 4) For comparison, synthetic α-FeOOH (Junsei Chemical Co. Ltd.) was also used.…”
Section: Methodsmentioning
confidence: 99%
“…5) A Se(VI) solution was prepared by dissolving sodium selenate (Na 2 SeO 4 ) in 1×10 −2 M NaClO 4 to yield a working solution having a selenium concentration of 6×10 −4 M. The batch type sorption experiments of Se(VI) were carried out in a similar way as is described elsewhere. 4) The sorption experiments for Fe-montmorillonite were performed in an Ar-gas glove box to avoid the oxidation of Fe(II) until the introduction of Fe-montmorillonite to solution. The Se(VI) solution was not degassed to keep the oxidation state of Se(VI).…”
Section: Methodsmentioning
confidence: 99%
“…However, up to now no sorption data for americium and plutonium on OPA have been published. More sorption studies have been reported for the uptake of actinides by pure clay minerals, that are the main constituents of OPA (e. g., montmorillonite [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], illite [32][33][34][35][36][37][38][39][40], kaolinite [31,[41][42][43][44][45][46][47][48][49][50][51] , the cation exchange capacity was equal to 10 ± 4 meq/100 g for both powders [9,11]. The mineral composition and the content of the trace elements of the used OPA measured by X-ray fluorescence analysis are given elsewhere [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most ubiquitous inorganic colloids are aluminosilicate clays that are commonly observed as mobile colloids due to their inherently small particle size and prevalence as alteration minerals from original host rock material (Kersting et al, 1999). Clays are known to sorb Pu Keeney-Kennicutt and Morse, 1985;Kozai et al, 1996;Kozai et al, 1993;Lujaniene et al, 2007;Powell et al, 2004Powell et al, , 2005Powell et al, 2008;Sabodina et al, 2006;Sanchez et al, 1985;Turner et al, 1998). In addition, the proposed use of bentonite within some engineered barrier systems scenarios for high-level nuclear waste repositories provides additional importance to understanding Pu interaction with smectite aluminosilicate clays (Sabodina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%